2012
DOI: 10.5665/sleep.1698
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia in Patients with COPD

Abstract: Insomnia disorder is highly prevalent in patients with COPD; current tobacco use and sadness/anxiety are associated with a higher prevalence, and oxygen use with a lower prevalence of insomnia; patients with insomnia have poorer quality of life and increased daytime sleepiness; and insomnia is associated with worse objective sleep quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
75
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 37 publications
4
75
2
4
Order By: Relevance
“…However, a recent study did not show an adverse influence of any inhalers on sleep. 4 In fact, univariate analyses revealed lower insomnia prevalence in patients on β-agonist inhalers, although the effects were not statistically significant in multivariate analyses. Inhaled steroids are commonly used in COPD, but their effect on sleep has not been systematically assessed.…”
Section: Etiologymentioning
confidence: 94%
See 4 more Smart Citations
“…However, a recent study did not show an adverse influence of any inhalers on sleep. 4 In fact, univariate analyses revealed lower insomnia prevalence in patients on β-agonist inhalers, although the effects were not statistically significant in multivariate analyses. Inhaled steroids are commonly used in COPD, but their effect on sleep has not been systematically assessed.…”
Section: Etiologymentioning
confidence: 94%
“…A recent study found a high prevalence of insomnia disorder (27.3%), defi ned as presence of insomnia symptoms along with daytime manifestations, in patients with COPD. 4 Whether COPD severity is related to worse sleep is unclear. Some studies suggest worse sleep in more severe COPD, 9 while other studies have not shown an association between FEV1 and reported sleep quality.…”
mentioning
confidence: 99%
See 3 more Smart Citations